Use of Salmon Cardiac Primary Cultures (SCPCs) of different genotypes for comparative kinetics of mx expression, viral load and ultrastructure pathology, after infection with Salmon Pancreas Disease Virus (SPDV). Issue 72 (January 2018) - Noguera, Patricia; Collet, Bertrand; Klinger, Matthias; Örün, Hristo; del Pozo, Jorge
Abstract: In vitro fish based models have been extensively applied in human biomedical research but, paradoxically, less frequently in the research of fish health issues. Farmed Atlantic salmon can suffer from several viral conditions affecting the heart. Therefore, species-specific, cardiac in vitro models may represent a useful tool to help further understanding and management of these diseases. The mechanisms underlying genotype based resistance are complex and usually rely on a combined effect of elements from both the innate and adaptive immune response, which are further complicated by external environmental factors. Here we propose that Salmon Cardiac Primary Cultures (SCPCs) are a useful tool to investigate these mechanisms as the basis for genotypic differences between Atlantic salmon families in susceptibility to cardiotropic viral disease. Using SCPCs produced from two different commercially available Atlantic salmon embryonated ova (Atlantic Ova IPN sensitive" (S) and "Atlantic QTL-innOva ® IPN/PD" (R)), the influence of host genotype on the viral load and mx expression following Salmon Pancreas Disease Virus infection was assessed over a 15 day period. Both R and S SCPCs groups were successfully infected. A measurable difference between groups of viral nsP1 and host antiviral mx gene expression was observed (i.e. a later, but larger onset of mx expression in the R group). Mx expression peaks were followed by a decrease in viral nsP1 in both groups. Additionally, ultrastructural examination of infected SCPCs allowed the description of degenerative changes at the individual cell level. The SCPC model presents some advantages, over current fish cell culture monolayers and in vivo material, such as the presence of different cell components normally present in the target organ, as well as the removal of a layer of functional complexity (acquired immunity), making it possible to focus on tissue specific, early innate immune mechanisms. These preliminary results highlight the importance of considering genetic origin when selecting the fish source for the production of SCPCs, as well as their usefulness as screening tools for assessment of genotypic differences in disease resistance. Highlights: SCPCs represent as a useful tool to investigate fish cardiotropic viral conditions. Using a disease resistance trait, genotypic screening with SCPCs seems possible. Host mx and viral nsP1 expressions showed differences after SPDV infection. There was a later but larger onset of mx expression in the resistant genotype SCPCs. Ultrastructural examination shows single cell degenerative changes from 24hpi.